Aplikasi massage effleurage menggunakan minyak aromaterapi mawar untuk mengurangi dismenore - Nursangadah, Siti; Rohmayanti, Rohmayanti; Hidayah, Nurul (Universitas Muhammadiyah Magelang, 2021)
Background: Menstruation is a normal process that happens from the puberty to menopause stage among healthy women. Healthy women get menstruation once in a month during the reproductive age. During the menstruation, women experience physical discomforts, such as pain. Dysmenorrhea is the common pain. A non-phramacology treatment were needed to reduce the pain and effleurage massage using rose aromatherapy is one of the method that can be used. Aim: The aim of this study was to determine the effectivity of effleurage massage using rose aromatherapy in reducing dysmenorrhea. Method: This study was a case study method and the sampling technique was a purposive sampling. The sample for this case study was a 16 year old female teenage patient who experienced dysmenorrhea and the scale was 6. The data collection in this study was using participatory observation methods, unstructured interviews, and documentation. The data were analyzed using the analysis domain. Result: The results showed that effleurage massage therapy using rose aromatherapy oil could reduce dysmenorrhea from a scale of 6 to 2 within three days of intervention. Conclusion: Effleurage massage is useful for reducing hypoxia in tissues. Thus, there is an increasing level of oxygen in the tissue and could reduce the pain. On the other hands, rose aromatherapy has effect as a local analgesic and antispasmodic. Therefore, effleurage massage therapy using rose aromatherapy oil can be suggested to young women with dysmenorrhea.